Gestão de dados pessoais: uma análise de casos concretos a partir do ordenamento jurídico brasileiro - Oliveira, Tassyara Onofre de (2017)
This research investigates the protection of personal data within the Brazilian legal system, in order to unravel the level of protection and how this is effected. Therefore, the objective is to identify the Brazilian legislation that deals with the protection of personal data. Identifies the challenges for managing personal data in Brazil, establish some practical cases in the national and international levels. It aims, therefore, to seek solutions through legislation already regarded in Brazil for cases of resolutions. Finally, it maps the laws and practices of other countries, compared with those from Brazil, with the aim of presenting new solutions to the loopholes in Brazilian laws. As for the method, the research appears as qualitative primarily based on documentary evidence. It is hoped that this research, at its end, identifies personal data management practices in Brazil.